Possibilities of Formation, Diagnostics and Monitoring of Axiological Competences of Technical University Students - O. A. Volkova; E. P. Shebolkina (Высшее образование в России)
The article highlights the need to supplement the basic parameters of engineering education with an axiological component. The authors emphasize that the main problem of the current higher technical education is not the quality of professional competencies, but low humanization, which results in an underestimated social significance of engineering professions, as well as a focus on extracting benefits without taking into account the consequences of man-made impacts. The process of humanization of engineering education is possible with its value modification through the development of axiological competencies. The authors substantiate the structure of axiological competences, give the results of expert analysis of their content features in relation to higher technical education, define safety as a key concept in the interpretation of the essence of axiological competences of the engineering professional field. The analysis of domestic and foreign studies of the concept of «safety» as a value, system competence and purpose of engineering education is given, the term «save-attitude» is highlighted. The process of formation of axiological competences in higher education is a longitudinal educational work, an example of which is the educational program «Life-orientation workshop» approved by the authors. The article suggests possible means of diagnostics of axiological competences components and ways of estimation of their development, describes a pedagogical experiment, the results of which allow them to draw a conclusion about the effectiveness of both the educational program and monitoring forms of diagnostics of axiological competencies.